Self‐perceived health status and mental health outcomes in young adults born with less than 1000 g. (28th December 2012) - Natalucci, G; Becker, J; Becher, K; Bickle, GM; Landolt, MA; Bucher, HU
Abstract Aim To assess self‐perceived health status and mental health outcomes of former extremely low‐birth‐weight (ELBW) infants at young adulthood compared with community norms and to analyse predictors of poor outcome. Methods Fifty‐five ELBW adults, 18 men (33%), with median (range) gestational age of 28.7 (25.0–34.0) weeks and birth weight of 930 (680–990) grams, born in Switzerland, were included. They self‐rated their health status and mental health at a mean (range) age of 23.3 (21.8–25.9) years. Health status was measured by the Medical Outcomes Study Short Form‐36 questionnaire and mental health by the Brief Symptom Inventory. Results The mean scores for both outcome measures were in the normal range. However, the study group self‐rated significantly higher physical health status and lower mental health status compared with the community norms, and scores for self‐perceived mental health tended to be worse in the former. ELBW adults reported more problems in socio‐emotional role functioning compared with the community norms. Female sex was associated with poorer and bronchopulmonary dysplasia with better mental health status. Conclusion Health status and mental health of former ELBW adults were overall satisfying. However, the comparison with the community norms revealed differences, which may be important for parental and patient counselling and developing support strategies.